EKSPLORASI KONSEP GEOMETRI PADA GAME MOBILE LEGENDS - Nurul Husnah Mustika Sari; Fika Luthfia Sari; Miftakhur Rizqoh; Aditian Fani; Aditiya Nasocha Prasetiyo (INSPIRAMATIKA, 2022)
Technological changes and developments have resulted in changes in human culture and habits, both adults, teenagers and even children. Seeing that civilization itself has shifted with the emergence of a new era where at this time humans have been side by side with the internet. The word online is already familiar to the public, one of the things that is currently often the subject of discussion has even become a prestigious event on television, namely the Mobile Legends E-sport tournament. This study aims to explore the concept of geometry in the Mobile Legends game. The data collection technique of this research is observation and documentation technique. Checking the validity of the data is done by triangulation. The results of the study show that in the Mobile Legends game there are flat shapes such as circles, ellipses, squares, rectangles, triangles, regular polygons, and irregular polygons. Then there are the geometrical concepts of congruence and congruence, geometry transformation, and pyramid. These geometric concepts can be used in learning mathematics at school.